Lincoln tells a joke : how laughter saved the president (and the country) - Krull, Kathleen. (Harcourt Children's Books/Houghton Mifflin Harcourt, 2010)
A biography of one of America's greatest presidents, focusing on his use of wit and humor, and his love of language.